Take me out to the ball game [videorecording (DVD)] - Berkeley, Busby, 1895-1976; Sinatra, Frank, 1915-1998; Kelly, Gene, 1912-1996; Williams, Esther, 1921-2013 (Frank Sinatra collection (Turner Entertainment Co.), 2008)
Singing, dancing baseball players Dennis Ryan and Eddie O'Brien find their friendship tested when both fall for the new, female owner of their team.